RATU KEMALA SARI DAN PERDAGANGAN GELAP DI KALIMANTAN SELATAN PADA ABAD XIX MASEHI - Andi Nuralang (Balai Arkeologi Kalimantan Selatan, 2008)
Ratu Kemala Sari is as well-known salt entrepreneur in the southeast region of Kalimantan. She is the spouse of Sultan Adam. In the 19th Century smuggling was one of the most troubling social phenomenon concerned by the sultanate and the people as well. Salt being the most important commodity at that time was also subject to smuggling. Why was salt considered valuable to be smuggled? How was the condition of trade monopoly in the southeastern part of Kalimantan? This article will discuss the position of Ratu Kemala Sari as famous salt enterprenuer and her role as a leading figure for business, economic and politic in the southeastern part of Kalimantan, especially during the reign of Sultan Adam.